Facilitation of non-nociceptive bladder activity and suppression of somatic afferent inhibition by hypogastric afferents in cats - Shen, Bing; Wang, Jicheng; Tai, Changfeng; Beckel, Jonathan M. (Frontiers in Neuroscience, 2025)
IntroductionWhile it is well known that the sensory arm of the micturition reflex is mediated by A-δ afferents in the pelvic nerve, the urinary bladder is also innervated by afferents in the hypogastric nerve (HGN), whose role in micturition is less well understood. We have recently determined that stimulation of HGN afferents can facilitate nociceptive bladder activity in the cat induced by intravesical instillation of acetic acid. The aim of the present study, then, was to determine if activation of HGN afferents could similarly facilitate normal bladder activity in the cat, evoked by saline distension. Additional experiments examined if HGN stimulation could modulate the inhibitory effects of tibial or pudendal neuromodulation on bladder capacity.MethodsContinuous infusion cystometry was performed in 9 (4 male, 5 female) α-chloralose anesthetized cats in which the HGNs were transected bilaterally. Bipolar electrodes were used to stimulate the central end of the cut HGNs at varying intensities (1-15 V) and frequencies (1-40 Hz) during bladder filling with saline (1-2 ml/min) until a micturition contraction occurred. Tripolar cuff electrodes were also placed on the left pudendal and left tibial nerve to examine the effect of neuromodulation on bladder capacity during cystometry.ResultsHypogastric nerve stimulation (HGNS) at 30 Hz and 15 V significantly reduced bladder capacity to 80.01 ± 3.86% of control. Tibial or pudendal nerve stimulation (5 Hz, 2 T) significantly increased bladder capacity to 187.6 ± 20.2% or 193.8 ± 19.0% of control, respectively. Simultaneous HGNS significantly reduced the efficacy of tibial nerve neuromodulation (reduced to 158.7 ± 18.7% of control) and but only partially suppressed the bladder inhibition induced by pudendal neuromodulation (reduced to 161.9 ± 18.0% of control).ConclusionThese results suggest that HGN afferents (possibly C-fiber nociceptors) from the bladder or other pelvic organs may facilitate normal bladder activity to cause bladder overactivity. Additionally, HGN afferents may influence the efficacy of tibial or pudendal neuromodulation therapy in treating OAB.